Recent advances on copper-catalyzed asymmetric synthesis and potential biological applications - Hoorub Ahmad; Muhammad Bilal; Tahir Maqbool; Nasir Rasool; Syed Adnan Ali Shah; Zainul Amiruddin Zakaria (Elsevier B.V., 2023)
An asymmetric catalysis is a form of catalytic reaction wherein a chiral catalyst controls the production of a chiral molecule to favour the synthesis of one stereoisomer over another. It’s a good way to make stereoisomeric molecules for pharmacological purposes. Among the transition metals, copper is a cost-effective, plentiful, and less poisonous metal. This review focused on the asymmetric transformations in the last fifteen years.